Trichromatic High Resolution-LBIC: A System for the Micrometric Characterization of Solar Cells - Navas, Javier; Alcántara, Rodrigo; Fernández-Lorenzo, Concha; Martín-Calleja, Joaquín (IntechOpen, 2011)
None